2011
DOI: 10.1073/pnas.1104991108
|View full text |Cite
|
Sign up to set email alerts
|

EBV nuclear antigen EBNALP dismisses transcription repressors NCoR and RBPJ from enhancers and EBNA2 increases NCoR-deficient RBPJ DNA binding

Abstract: EBV nuclear antigen 2 (EBNA2) and EBV nuclear antigen LP (EBNALP) are critical for B-lymphocyte transformation to lymphoblastoid cell lines (LCLs). EBNA2 activates transcription through recombination signal-binding immunoglobulin κJ region (RBPJ), a transcription factor associated with NCoR repressive complexes, and EBNALP is implicated in repressor relocalization. EBNALP coactivation with EBNA2 was found to dominate over NCoR repression. EBNALP associated with NCoR and dismissed NCoR, NCoR and RBPJ, or NCoR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…S2). Overall, EBNA2/RBPJ had more RBPJ signals than RBPJ-only sites genome-wide, consistent with the previous finding that EBNA2 significantly increased RBPJ association with a limited number of enhancer or promoter DNA sites (25). Motifs.…”
Section: Resultssupporting
confidence: 79%
“…S2). Overall, EBNA2/RBPJ had more RBPJ signals than RBPJ-only sites genome-wide, consistent with the previous finding that EBNA2 significantly increased RBPJ association with a limited number of enhancer or promoter DNA sites (25). Motifs.…”
Section: Resultssupporting
confidence: 79%
“…This suggested that HPV8 E6 can bind to NOTCH-responsive RBPJ target sites. MAML binding to RBPJ requires a composite ICN/RBPJ binding groove, and thus MAML cannot bind either of the factors independent of the other (18). It has been reported that HPV8 E6 binds to MAML directly and subsequently indirectly to RBPJ and ICN (9).…”
Section: Figmentioning
confidence: 99%
“…The HES1 promoter has two well-characterized RBPJ binding sites adjacent to the promoter that are required for NOTCH-mediated transcription (17). An additional RBPJ binding site important for HES1 expression in response to NOTCH activation approximately 5,000 bp upstream of the promoter has also been described (18). These sites in the HES1 enhancer (forward, 5= CCTCCCAGGATAGCTCTTG 3=; reverse, 5= TTTGCCT GAGGACTTGAAGC 3=) and promoter (forward, 5= CAAGACC AAAGCGGAAAGAA 3=; reverse, 5= GGTACCTGTGTGATCCCT AGGC 3=) were assessed using specific primer pairs (Fig.…”
Section: Figmentioning
confidence: 99%
“…EBNA2 is tethered to cell DNA mostly through RBPJ (11). EBNA2 is similar to its cell counterpart, Notch, which induces RBPJ DNA binding (22). RBPJ ChIP-seq signals also distinguish ESEs from ETEs (26).…”
mentioning
confidence: 99%
“…Its C-terminal transactivation domain recruits basal transcription machinery and activates gene transcription (11,(18)(19)(20). EBNALP coactivates with EBNA2 by removing repressors (21,22). EBNA3C binds to the p14 ARF promoter and represses CDKN2A expression (23,24), whereas EBNA3A binds to sites further upstream of CDKN2B (25).…”
mentioning
confidence: 99%